Vaccination response to tetanus toxoid and 23-valent pneumococcal vaccines following administration of a single dose of abatacept: a randomized, open-label, parallel group study in healthy subjects - Tay, Lee; Leon, Francisco; Vratsanos, George; Raymond, Ralph; Corbo, Michael (Arthritis research & therapy, 2007)
The effect of abatacept, a selective T-cell co-stimulation modulator, on vaccination has not been previously investigated. In this open-label, single-dose, randomized, parallel-group, controlled study, the effect of a single 750 mg infusion of abatacept on the antibody response to the intramuscular tetanus toxoid vaccine (primarily a memory response to a T-cell-dependent peptide antigen) and the intramuscular 23-valent pneumococcal vaccine (a less T-cell-dependent response to a polysaccharide antigen) was measured in 80 normal healthy volunteers. Subjects were uniformly randomized to receive one of four treatments: Group A (control group), subjects received vaccines on day 1 only; Group B, subjects received vaccines 2 weeks before abatacept; Group C, subjects received vaccines 2 weeks after abatacept; and Group D, subjects received vaccines 8 weeks after abatacept. Anti-tetanus and anti-pneumococcal (Danish serotypes 2, 6B, 8, 9V, 14, 19F and 23F) antibody titers were measured 14 and 28 days after vaccination. While there were no statistically significant differences between the dosing groups, geometric mean titers following tetanus or pneumococcal vaccination were generally lower in subjects who were vaccinated 2 weeks after receiving abatacept, compared with control subjects. A positive response (defined as a twofold increase in antibody titer from baseline) to tetanus vaccination at 28 days was seen, however, in ≥ 60% of subjects across all treatment groups versus 75% of control subjects. Similarly, over 70% of abatacept-treated subjects versus all control subjects (100%) responded to at least three pneumococcal serotypes, and approximately 25–30% of abatacept-treated subjects versus 45% of control subjects responded to at least six serotypes.